Fenomena Marriage is Scary di Kalangan Generasi Z : Tinjauan Hukum Islam dan Hukum Positif di Indonesia - Olviyani, Gita; Pramitha Sari, Indah; Ys, Rif’al Fauzi; Devito, Dani; M.Putra, Victor Pratama (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
Recently, the phenomenon of “Marriage Is Scary” emerged among young generations, especially Gen Z, reflecting fear and resistance toward the institution of marriage. This study aims to analyze the “Marriage Is Scary” trend from the perspectives of Islamic law and Indonesian positive law and to understand the implications of government regulations and programs in responding to this phenomenon. Using normative legal research with a contextual approach, this study examines Islamic legal sources and Indonesian legislation relevant to marriage. The study reveals that in Islamic law, marriage is categorized into five rulings (obligatory, recommended, permissible, disliked, and forbidden) with strong emphasis on physical, mental, and spiritual readiness of prospective spouses. From the perspective of positive law, regulations such as the Marriage Law, the Law on the Elimination of Domestic Violence, and Marriage Guidance Programs are government efforts to foster harmonious families as a response to emerging concerns. Government regulations and programs play a strategic role in addressing the “Marriage Is Scary” trend by emphasizing education, readiness, and legal protection in marriage.